Soil moisture–atmosphere coupling amplifies the change in extreme heat in inner East Asia under rapid summer warming - Zejiang Yin; Buwen Dong; Song Yang; Wei Wei (Environmental Research Letters)
Inner East Asia (IEA) is an important component of the global grassland ecosystem and has experienced a more rapid increase in extreme surface air temperatures compared to the summer mean in recent decades (2001–2020, relative to 1971–1990). This excess hot-extreme warming (EHEW) is particularly pronounced in the southern IEA, where extremely hot temperatures have increased twice as quickly as the summer mean warming, which itself already exceeds global-land warming by more than threefold. A quantitative analysis based on a Lagrangian temperature-anomaly equation along air-parcel backward trajectories initiated on hot days across IEA reveals that the observed EHEW is primarily attributable to increased diabatic heating, which predominantly occurs from 2 days before to the hot days. Meanwhile, changes in heat-prone synoptic-scale circulation only exert a limited influence on the excess warming. Soil drying within IEA appears to be a critical factor contributing to increased diabatic heating through soil moisture–atmosphere coupling, as it limits evaporation and enhances sensitive heat flux, thereby triggering positive soil moisture-temperature feedback. Our analysis underscores the significant impact of local soil moisture deficits on the intensified extreme heat. Urgent implementation of grassland and livestock management strategies, coupled with drought mitigation measures, is essential for adaptation and ecosystem conservation.